Pengaruh Model Pembelajaran Complete Sentence terhadap Kemampuan Menulis Teks Berita - Shinta Uly Monalisa Sihombing; Tigor Sitohang; Sarma Panggabean (Journal of Language Education (JoLE), 2023)
The purpose of this research is to develop reading materials using digital media. The advantage of this research is that the use of digital media as a learning tool can be used as a reference in providing alternative reading materials that suit the needs of students. This activity involves analyzing and organizing complex skills such as learning, thinking, reasoning, assimilation, and problem solving. First, the media as a support for learning, and the second is the media as a source of learning. Reading Indonesian texts for foreign speakers presents its own challenges in learning it. Reading has several skills that must be mastered. The habit of practicing reading greatly help you improve your reading skills. Using digital media can improve word reading skills. You should also be able to interpret and understand the words in the text. Keywords: reading, teaching materials, curriculum, development Model pembelajaran complete sentence adalah model pembelajaran yang dapat meningkatkan kemampuan siswa dalam menulis teks berita karena menuntut siswa untuk mengaitkan informasi yang satu dengan yang lainnya. Penelitian ini dilakukan untuk mengetahui pengaruh model pembelajaran complete sentence terhadap kemampuan siswa menulis teks berita. Penelitian ini menggunakan metode penelitian kuantitatif eksperimen dengan menguji data nilai siswa pada kelas eksperimen dan kelas kontrol. Hasil dari penelitian ini menunjukan bahwa model complete sentence berpengaruh terhadap kemampuan menulis teks berita siswa hal tersebut dibuktikan dengan rata-rata nilai siswa pada kelas eksperimen lebih tinggi daripada kelas kontrol yaitu rata-rata untuk kelas eksperimen sebesar 70,2 dan rata-rata kelas kontrol sebesar 45,06. Kata Kunci: model complete sentence, teks berita, kemampuan menulis.